PENGARUH PANCA USAHA TANI TERHADAP TINGKAT PRODUKSI PADI SAWAHDI KENAGARIAN UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - -, M. Abror - (Pendidikan Geografi, 2014)
The agricultural sector is a source of food supplies and raw materials required are implemented in a Negara.Penelitian Kenagarian Edge Ivory Crossing the Valley District of West Pasaman with the purpose of viewing and analyzing about: the effect of tillage, seed selection, irrigation, fertilization and pest control on the level of rice production in the five farm implement in District Valley Crossing West Pasaman. This type of research is "Descriptive Correlational. Study population was all rice farmers in the district, amounting to 8633 Valley Crossing KK. The sample of respondents was determined using proportional random sampling taken by 25% so that the sample amounted to 63 families. Based on the results of hypothesis testing, it can be concluded as follows: (1) There is the influence of tillage on the level of rice production in fulfilling the five farms in the District Valley Crossing West Pasaman because the contribution is very small (2.85%). (2) There is the influence of seed selection on the level of rice production in the five farm implement in District Valley Crossing West Pasaman because the contribution is very small (3.13%). (3) There is no effect of irrigation on rice production levels in implementing the five farms in Subdistrict Transverse Valley West Pasaman because the contribution is very small (0.19%). (4) There is a fertilization effect on the level of rice production in the five farm implement in District Valley Crossing West Pasaman because the contribution is very small (3.84% ). (5) There is no effect of pest control on rice production levels in implementing the five farms in the District Valley Crossing West Pasaman because the contribution is very small (0.13%). (6) There are influences together, tillage , seed selection, irrigation, fertilization and pest control on the level of rice production due to the contribution of including very small (4.84%)